Study on movement characteristics and numerical simulation of high-altitude rockfall in babao mountain in China - Yang, Yuanxiang; Zhang, Yuguang; Teng, Zimeng; Liu, Pin; Qiao, Lan (Frontiers in Earth Science, 2023)
High-altitude rockfalls, as one of the major geological disasters in mountains, is highly concerned about the study of failure mechanisms and disaster prevention and mitigation. In August 2020, the Babaoshan cliff in Yanhe County, Guizhou collapsed and falling rocks hit agricultural vehicles on the road and damaged residents’ houses below. Based on on-site investigation, three rockfall types of tension-rotating, tension-shear-falling, compression-shear exist in the study area, and the compression-shear rockfall can conform to the chain law of rockfall. The paper used the dynamic analysis software Rocpro-3D to simulate and invert the movement characteristics and impact range of rockfall at Babaoshan cliff. The results show that: 1) the hazardous zone, which is about 95 m wide and 175 m long, was formed by the rockfall at R1 and covered localized roads and houses below, with the covered probability of 20%, 17% respectively; 2) the terrains on the rockfall paths in two rockfall disaster events are mainly characterized by stepped shape and overall flat angle respectively, and the behaviors are mainly characterized by ejection and rolling respectively, meanwhile, the times to reach the road and houses were 17 s and 24.3 s, respectively, in addition, the protruding rock mass below the rockfall location gives the falling rock horizontal velocity and good movement space, which will make the falling rock move further away; 3) the different rockfall directions reflect different terrain combinations, simulation inversions reveal that different terrain combinations have significant control over the distance and shape of the rockfall trajectories. And, it was found that the more times a falling rock is rebounded, the greater the energy obtained; 4) the probabilities of falling rocks at H1, H2, H3 invading residential areas are respectively 8.67%, 20%, 19.33%, meanwhile invading road zone are respectively 10.67%, 15.33%, 9.33%. At least one point or several points stopped within the zone of the affected houses in the rockfall disaster event 2 in three prediction of the rockfall impact range, which indicates that there is a great risk that this house will continue to be affected by disasters after rockfalls occur within the steep cliff area above.